Difference in dry matter accumulation with variable rates of sulphur and potassium application under calcareous soils in Brassica napus vs. B. juncea - Amanullah; Muhammad Hassan Khan (Journal of Oilseed Brassica, 2026)
Improper sulphur (S) and potassium (K) fertilizer management decrease dry mater (DM) accumulation andyield in Brassica under calcareous soils. A field experiment was conducted at The University of Agriculture,Peshawar, Pakistan. The main objective of this study was to evaluate the effect of S and K fertilization onDM accumulation of Brassica species under calcareous soil at the study area. The experiment wasconducted in a randomized complete block design using three replications. Each replication consisted of 20treatments having two Brassica species [rape (B. napus) and Indian mustard (B. juncea)], three rates of S(15, 30, and 45 kg ha-1), three rates of K (30, 60, and 90 kg ha-1) and one control (no S and K applied). TheDM accumulation at various growth stages increased with K and S fertilization as compared to the zero-S/zero-K control plots. Both species responded positively to K and S fertilization, but the magnitude of responsevaried with levels of S and K. It was concluded that a combination of 60 kg K + 30 kg S ha-1 could improveDM accumulation and yield in Brassica species.